Association Between Malnutrition and Clinical Outcomes in the Intensive Care Unit: A Systematic Review. (July 2017) - Lew, Charles Chin Han; Yandell, Rosalie; Fraser, Robert J. L.; Chua, Ai Ping; Chong, Mary Foong Fong; Miller, Michelle
Malnutrition is associated with poor clinical outcomes among hospitalized patients. However, studies linking malnutrition with poor clinical outcomes in the intensive care unit (ICU) often have conflicting findings due in part to the inappropriate diagnosis of malnutrition. We primarily aimed to determine whether malnutrition diagnosed by validated nutrition assessment tools such as the Subjective Global Assessment (SGA) or Mini Nutritional Assessment (MNA) is independently associated with poorer clinical outcomes in the ICU and if the use of nutrition screening tools demonstrate a similar association. PubMed, CINAHL, Scopus, and Cochrane Library were systematically searched for eligible studies. Search terms included were synonyms of malnutrition, nutritional status, screening, assessment, and intensive care unit . Eligible studies were case-control or cohort studies that recruited adults in the ICU; conducted the SGA, MNA, or used nutrition screening tools before or within 48 hours of ICU admission; and reported the prevalence of malnutrition and relevant clinical outcomes including mortality, length of stay (LOS), and incidence of infection (IOI). Twenty of 1168 studies were eligible. The prevalence of malnutrition ranged from 38% to 78%. Malnutrition diagnosed by nutrition assessments was independently associated with increased ICU LOS, ICU readmission, IOI, and the risk of hospital mortality. The SGA clearly had better predictive validity than the MNA. The association between malnutrition risk determined by nutrition screening was less consistent. Malnutrition is independently associated with poorer clinical outcomes in the ICU. Compared with nutrition assessment tools, the predictive validity of nutrition screening tools were less consistent.